Legal Resolution of Same-Sex Relationships in Indonesia - Muhammad Rafi Riyadi; Rosalia Dika Agustanti (Universitas Muhammadiyah Sumatera Utara, 2026)
This research is motivated by the social fact that same-sex relationships in Indonesia remain a sensitive issue, giving rise to tensions between moral values, religious views, and the national legal framework. Although consensual same-sex relationships between adults are not criminalized in the Criminal Code, there are regulatory ambiguities, the potential for indirect criminalization through moral norms, and the existence of several regional regulations that restrict the freedom of movement of LGBT groups. This research aims to analyze the applicable legal regulations regarding same-sex relationships and formulate a relevant legal settlement model in the Indonesian context. The issues include how the law regulates same-sex relationships in Indonesia and how the legal settlements are handled. The research uses a normative legal method with a statutory approach and a case approach utilizing secondary data. The results show that national legal regulations are still not uniform and tend to be influenced by majority moral norms, thus creating uncertainty in the protection of individual rights. Furthermore, the proposed legal settlement emphasizes the importance of regulatory harmonization, a non-discriminatory approach, and the protection of human rights as the basis for a more just settlement. This research emphasizes the need for clearer and more inclusive legal reforms to address Indonesia's evolving social dynamics.